Effect of volume fraction and unidirectional orientation controlled graphite on thermal properties of graphite/copper composites. (15th February 2020) - Jang, Jun-Ho; Park, Hyun-Kuk; Lee, Jeong-Han; Lim, Jae-Won; Oh, Ik-Hyun
Abstract: This study aims to investigate the effect of the orientation of Gr powder and the volume fraction of Cu and Gr on the thermal conductivity (TC) and coefficient of thermal expansion (CTE) of Cu-Gr composites. Coarsening Gr flake (CGF) powder was coated with Cu through electroless plating (EP) method and was then sintered using pulsed current activated sintering. The present study confirmed that the presence of Cu oxide layer formed between Cu layer and CGF powder via electroless plating process and how it decomposes during the pulsed current activated sintering process. The anisotropy Gr has different characteristics depending on the bonding direction. In order to control the bonding direction of outstanding thermal properties of Gr, a stacking-pressing process was carried out, and the thermal conductivity was measured. The TC and CTE of Cu-Gr composites were measured in the longitudinal and transverse direction according to difference of Cu-Gr volume fraction, and were compared with theoretical value.